2019
DOI: 10.1371/journal.pone.0210502
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of cardiac diagnostic testing for acute coronary syndrome in the Brazilian healthcare system: A national geospatial evaluation of health access

Abstract: BackgroundLittle is known about the utilization of cardiac diagnostic testing in Brazil and how such testing is related with local rates of acute coronary syndrome (ACS)-related mortality.Methods and resultsUsing data from DATASUS, the public national healthcare database, absolute counts of diagnostic tests performed were calculated for each of the 5570 municipalities and mapped. Spatial error regression and geographic weighted regression models were used to describe the geographic variation in the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
(33 reference statements)
1
8
0
3
Order By: Relevance
“…Nessa avaliação geoespacial nacional do acesso à saúde, mortalidade por SCA foi associada a menor renda, assim como à realização de menor número de exames nucleares e maior número de testes de esforço e de cateterismos cardíacos. 127 • Um estudo usando metodologia de microcusto avaliou os custos associados com ICP em 40 pacientes de dois hospitais públicos de ensino em 2017. O custo mediano de ICP foi R$ 4.579 em um hospital e R$ 3.156 em outro.…”
Section: Mortalidade Relacionada à Cirurgia De Revascularização Do Mi...unclassified
“…Nessa avaliação geoespacial nacional do acesso à saúde, mortalidade por SCA foi associada a menor renda, assim como à realização de menor número de exames nucleares e maior número de testes de esforço e de cateterismos cardíacos. 127 • Um estudo usando metodologia de microcusto avaliou os custos associados com ICP em 40 pacientes de dois hospitais públicos de ensino em 2017. O custo mediano de ICP foi R$ 4.579 em um hospital e R$ 3.156 em outro.…”
Section: Mortalidade Relacionada à Cirurgia De Revascularização Do Mi...unclassified
“…Easy access to healthcare centers lowers the mortality and morbidity generally [8]. However, some studies have shown that the healthcare resources are unequally distributed across regions in Brazil [9]. Thus, geostatistical tools such as spatial analysis to verify the geographically variance of IHD risks could increase the optimization of healthcare resource allocations [10].…”
Section: Introductionmentioning
confidence: 99%
“…Aging rate was expected to be related to IHD mortality. However, illiteracy and accessibility indexes that are often discussed in scientific literature but not specifying its real importance and weight [ 3 , 7 , 8 ] were important for index formation and can be considered in public policies to reduce mortality. Examples are increasing the number of ambulances as well as the differential management of patients who are more than 120 minutes from the reference hemodynamics centers.…”
Section: Discussionmentioning
confidence: 99%
“…Brazil had an average of 306 IHD deaths daily, or one death every five minutes [ 2 ]. Cardiac diagnostic tests availability are limited, mostly occurring in urban centers [ 3 ], disproportionately limiting the accessibility of remote population and those from small cities.…”
Section: Introductionmentioning
confidence: 99%